Determining the optimal post-graduation path for accounting students of National University-Manila : an analysis of having SAP training - Devosora, Kryzdelle Jean; Del Rosario, Dorothy Joy; Castillo, Jascha Richer; Runas, Janalyn; Macadindang, Mujahidah; Clarito, Trisha Kareen (Manila : National University, 2024)
This research aims to explore the optimal post-graduation path for accounting graduate students at National University - Manila by analyzing the impact of SAO traning on their employability.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation of data -- Chapter 5. Summary of Findings, Conclusions, Analysis and Interpretation of Data -- References.
Includes bibliographical references.